Stratigraphy and age of the human footprints-bearing strata in Jeju Island, Korea: Controversies and new findings. (December 2015) - Sohn, Y.K.; Yoon, W.S.; Ahn, U.S.; Kim, G.B.; Lee, J.-H.; Ryu, C.K.; Jeon, Y.M.; Kang, C.H.
Abstract: The age of the human footprints found on the bedding plane of a reworked volcaniclastic deposit on Jeju Island, Korea, has been a subject of controversies in Korea for more than a decade. Two researchers that discovered the footprints and their colleagues have argued that the footprints belong to Paleolithic 'hominids' that lived in the Late Pleistocene (c. 19, 000–25, 000 cal yrs BP). They made their argument on the basis of the pre-Holocene radiocarbon ages of humic and humin organic matter in bulk sediment, but have ignored Holocene radiocarbon ages of mollusk shells and other age data from the volcaniclastic deposit and adjacent geologic units. They also refused to correlate the deposit with any well-defined and well-dated stratigraphic units in the study area but correlated it with an imaginary stratigraphic unit which they named "unnamed strata". This study discusses the problems of their work published in a series of papers in the last decade by reviewing the stratigraphy and age of the geologic units in southwestern Jeju Island and presenting new sedimentologic and stratigraphic observations and new radiocarbon dating of mollusk shells. This study shows that the "unnamed strata" is the basal part of the Songaksan Tuff, which is the rimbeds of a coastal tuff ring that erupted c. 3700 yrs BP, and that the strata at the footprints site comprise the distal Songaksan Tuff at the base and a reworked volcaniclastic deposit (the Hamori Formation) above it. The human footprints, which are found in the topmost part of the Hamori Formation, should therefore postdate the eruption of the Songaksan volcano and belong to late Neolithic 'humans' who lived in the mid- to late Holocene. Highlights: There are allegedly Late Pleistocene hominid footprints on Jeju Island, Korea. The argument is based on incorrect interpretation of the geology of Jeju Island. We show that the footprints lie above a 3700 yrs BP tephra layer. The footprints therefore belong to Neolithic humans who lived in the Holocene.